Princípio da eficiência como um direito difuso da cidadania: controle judicial de políticas públicas que visem à concretização dos direitos sociais sob a análise econômica do direito - Santana, Paulo Victor Pinheiro de (2014)
In face of the need to improve the provision of social rights in Brazil, the current work investigates the possibility of understanding the administrative efficiency principle, presented in article 37 of the Federal Constitution, as diffuse right capable of orienting the public policies which aim to provide the social rights, using as theoretical framework the Northamerican school of the Economic Analysis of Law. The work is made according to a bibliographic review, of Brazilian and foreign authors, regarding the themes of social fundamental rights, judicial control of public policies, efficiency and Economic Analysis of Law. First, one studies the fundamental rights and its ratings, in order to reach a delimitation of social rights. Based on such delimitation, one studies the public policies as a way of providing these rights, and also the reality of judicial control of these policies observed in Brazil nowadays, proposing limits to the legitimacy of such control. After that, one investigates the administrative efficiency principle, analyzing its genesis in Brazilian Law, the changes caused by its legalization, the different legal and economical concepts and the possibility of its reading as a diffuse right, judicially chargeable. At last, as theoretical framework for the judicialization of the efficiency of public policies, one studies the origin, the history, the compatibility and the possible contributions to Brazilian law of the school of Economic Analysis of Law. One concludes in defense of the judicialization of efficiency as a diffuse right, allowing the improvement of social rights’ public policies through a more pragmatic and consequentialist analysis of these rights. One proposes also the limited use as theoretical framework of the Economic Analysis of Law, as a way to make possible the analysis of efficiency in Brazilian law.